1997
DOI: 10.1016/s0022-5347(01)65087-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-Intercourse Versus Daily Ciprofloxacin Prophylaxis for Recurrent Urinary Tract Infections in Premenopausal Women

Abstract: Long-term post-intercourse prophylaxis with ciprofloxacin proved to be equally effective as daily prophylaxis, and the major advantage of the former therapy was use of only a third of the amount of drug consumed in daily prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(22 citation statements)
references
References 22 publications
0
19
0
3
Order By: Relevance
“…48 Additional uncontrolled trials have suggested equivalency of other antibiotic regimens. 8 Post-coital treatment involves taking a course of antibiotics within 2 hours of intercourse allowing for decreased cost and presumably side effects (Table 3).…”
mentioning
confidence: 99%
“…48 Additional uncontrolled trials have suggested equivalency of other antibiotic regimens. 8 Post-coital treatment involves taking a course of antibiotics within 2 hours of intercourse allowing for decreased cost and presumably side effects (Table 3).…”
mentioning
confidence: 99%
“…This is similar to previous studies, where no increased emergence of resistance was observed. 12,31 There were limitations to the present study. The study only followed patients for 12 months and included a relatively small sample.…”
Section: Discussionmentioning
confidence: 85%
“…One randomized control trial compared postcoital versus continuous daily ciprofloxacin and found no significant difference in rates of UTI, suggesting postcoital prophylaxis is as effective as daily prophylaxis. 12 Predisposing factors for UTIs in postmenopausal women are generally different from those in young women; for instance, long-distance walking or travelling can raise intra-abdominal pressure and temporarily aggravate incontinence, cystocele or postvoiding residual urine. 13 The present study assessed the effectiveness and safety of prophylactic single-dose antibiotics, taken after exposure to certain conditions associated with UTI recurrence, compared with continuous lowdose daily antibiotic prophylaxis in postmenopausal women.…”
Section: Antibiotic Prophylaxis For Recurrent Utimentioning
confidence: 99%
“…Postcoital antibiotic prophylaxis is considered to have an effect similar to continuous prophylactic drug administration. In a study in which 152 women with a history of recurrent UTI were randomly assigned to 2 groups and administered ciprofloxacin 125 mg daily or postcoitally, the occurrence rate decreased in both groups (3.66 to 0.031 episodes per year vs. 3.62 to 0.043 episodes per year), but the differences were not statistically significant (p=0.7) [23]. Drugs that can be used for postcoital antibiotic prophylaxis are presented Table 2.…”
Section: ) Postcoital Antibiotic Prophylaxismentioning
confidence: 99%